The Level of Education, Business Age and Knowledge of Food Additives and Methanil Yellow: A Study among Online Noodle Sellers (GoFood and GrabFood) in East Surabaya: Tingkat Pendidikan, Lama Berjualan dan Pengetahuan Mengenai Bahan Tambahan Pangan dan Methanil Yellow: Studi pada Pedagang Mi Online (Gofood dan Grabfood) di Surabaya Timur - Utari Gita Setyawati; Trias Mahmudiono (Universitas Airlangga, 2023)
Knowledge of food additives is one of the important factors for sellers. Knowledge affected the choice and usage of food additives for the product. Sellers’ knowledge influenced by various factors such as level of education and experience or business age. This study aimed to analyze the relationship between education, business age, and knowledge among noodle sellers who sell their product through online order-delivery application GoFood and GrabFood in East Surabaya. This research was an analytic observational study with a cross-sectional method. This study using 57 respondents who sell their noodles product through online order-delivery application GoFood and GrabFood in East Surabaya within 2.38 km from predetermined point, Campus C Airlangga University, Mulyorejo obtained using random sampling method. Respondent characteristics and knowledge data were collected through interview using questionnaire. Data was analyzed using Spearman Rank Test to find the relationship between variables. The result showed that majority of respondents had senior high school education level, business age 1-5 years, and low level of knowledge. The results showed that education has significant relationship with knowledge (p value=0.017) with correlation coefficient 0.314 and the insignificant relationship between business age and knowledge (p value=0.418). In conclusion, level of education played an important role in sellers’ knowledge of food additives. Socialization about the usage of food additives also need to be done regularly to prevent the false information received by the sellers.